2012
DOI: 10.1097/acm.0b013e318248ed0a
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Clerkship Module Focused on Patients With Disabilities

Abstract: Lack of medical training results in physicians being unprepared to provide care to people with disabilities, which, in turn, contributes to the substantial health disparities that are evident in this population. Few medical schools or primary care residencies address the care of adults with disabilities. Competencies and guidelines to assist American physicians in caring for patients with physical or intellectual disabilities have yet to be established, thus making educational goals unclear. This article descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 15 publications
0
47
0
Order By: Relevance
“…More challenging by far are attitudinal and knowledge barriers [ 40 ]. The literature is unanimous that physicians are inadequately prepared to deal with disabled patients and with disability issues in practice [ 16 , 39 , 41 , 42 ]. As an example, Junius-Walker and colleagues [ 24 ] found that physicians were ill-disposed toward problems associated with disability, particularly those to which there is no immediate medical solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More challenging by far are attitudinal and knowledge barriers [ 40 ]. The literature is unanimous that physicians are inadequately prepared to deal with disabled patients and with disability issues in practice [ 16 , 39 , 41 , 42 ]. As an example, Junius-Walker and colleagues [ 24 ] found that physicians were ill-disposed toward problems associated with disability, particularly those to which there is no immediate medical solution.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors and advocates have responded to this gap with guidelines and educational materials [ 43 ]; however the evidence suggests that knowledge products alone are insufficient to produce the kind of change needed to overcome systemic and physician barriers. Most effective appear to be experiential learning opportunities that bring medical trainees into contact with disabled people, in an environment characterized by collaboration and appropriate supervision [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although comfort level is not an indicator of competence or knowledge, it is an essential component in characterizing competent practitioners (Woodard, Havercamp, Zwygart, & Perkins, 2012). Given that our study did not investigate competence, we could not conclude that comfort level is equivalent to competence.…”
Section: Discussionmentioning
confidence: 83%
“…2,3 Of note, the University of South Florida School of Medicine has developed a robust disabilities curriculum in their primary care clerkship that incorporates didactic learning, home visits, and clinical experiences with individuals with disabilities to teach students how to deliver care in a sensitive, patientcentered manner. 3 Our curriculum, although not as comprehensive as that at the University of South Florida School of Medicine, adds a new and important guiding principle to the field-the explicit engagement of individuals with disabilities and consideration of their concerns during all phases of the planning and implementation of the The goals of the session were clear. 4.24 ± 0.69 The preparatory reading assignment (Web site "Models of disability") helped give me a basic understanding and overview of the social and medical models of disability.…”
Section: Next Stepsmentioning
confidence: 99%
“…We hope that these sessions will form the basis of a longitudinal curriculum, extending beyond the preclinical years. 3 Second, the evaluation we used to assess students' experience is of limited validity in assessing the overall educational value of the curriculum.…”
Section: Next Stepsmentioning
confidence: 99%